The Impact of Confucian Ethics on Social Harmony in Contemporary China - Jing, Li (Journal of Philosophy, Culture and Religion, 2024)
Purpose: The aim of the study was to analyze the impact of Confucian ethics on social harmony in contemporary China. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Confucian ethics strongly impact social harmony in contemporary China by promoting filial piety, respect for authority, and harmony in interpersonal relations. These values foster trust, cooperation, and stability within society. Integration of Confucian principles into government policies and education further enhances social cohesion and national unity. Unique Contribution to Theory, Practice and Policy: Confucianism and social harmony, modernization theory and confucianism & cultural relativism and confucian ethics may be used to anchor future studies on the impact of confucian ethics on social harmony in contemporary China. Schools and universities should integrate Confucian teachings into their moral education programs, emphasizing virtues such as filial piety, benevolence, and righteousness. Policies should be designed to incentivize behaviors that align with Confucian ideals, such as promoting filial piety through eldercare subsidies or fostering a culture of civility and respect in public spaces.